2020
DOI: 10.1038/s41598-020-69634-3
|View full text |Cite
|
Sign up to set email alerts
|

Elafin inhibits obesity, hyperglycemia, and liver steatosis in high-fat diet-treated male mice

Abstract: Elafin is an antimicrobial and anti-inflammatory protein. We hypothesize that elafin expression correlates with diabetes. Among non-diabetic and prediabetic groups, men have significantly higher serum elafin levels than women. Men with type 2 diabetes mellitus (T2DM) have significantly lower serum elafin levels than men without T2DM. Serum elafin levels are inversely correlated with fasting blood glucose and hemoglobin A1c levels in men with T2DM, but not women with T2DM. Lentiviral elafin overexpression inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Elafin is an antimicrobial and anti-inflammatory protein with a molecular weight of approximately 6 kDa ( 205 ). Lentiviral overexpression of elafin inhibits HFD-induced steatosis in mice ( 206 ). MPO has also been studied as a target of anti-neutrophil therapies because it mediates multiple steps in neutrophil-induced inflammation and tissue damage ( 207 ).…”
Section: Neutrophils As Potential Therapeutic Targets For the Treatment Of Nashmentioning
confidence: 99%
“…Elafin is an antimicrobial and anti-inflammatory protein with a molecular weight of approximately 6 kDa ( 205 ). Lentiviral overexpression of elafin inhibits HFD-induced steatosis in mice ( 206 ). MPO has also been studied as a target of anti-neutrophil therapies because it mediates multiple steps in neutrophil-induced inflammation and tissue damage ( 207 ).…”
Section: Neutrophils As Potential Therapeutic Targets For the Treatment Of Nashmentioning
confidence: 99%
“…56 It is unfeasible to define phenotype-based therapy in current clinical practice because most CD patients' phenotypes are unknown. We believe that the elafin-Eudragit FS30D formulation can cover intestinal inflammation and fibrosis because the same formulation inhibited obesity and hyperglycemia in high-fat diet-treated mice, 22 which had lowgrade chronic intestinal inflammation. 57 In summary, elafin inhibits cathepsin S-dependent PAR2 activity and reduces ZEB1 and collagen expression in intestinal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…8,21 Oral elafin formulation was as efficacious as lentiviral elafin overexpression in reversing obesity and diabetes in high-fat diet-treated mice. 22 Intravenous infusion of elafin to increase circulating levels (4.5 mg/mL) is also safe without affecting plasma elastase activity and cytokine levels in patients. 23 Therefore, elafin is an attractive therapeutic target against intestinal inflammation and fibrosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 366 Elsewhere, exosomal miR181b‑5p and miR219‑5p of immune cell origin that are induced by elafin (an anti-inflammatory protein) promote leptin expression in adipocytes to reduce food consumption, obesity, and hyperglycemia in HFD male mice. 378 It has been reported that aerobic exercise regulates serum exosomal miRNAs in obese mice. It decreases the levels of miR-122, miR-192, and miR-22, which are associated with improved adipogenesis, insulin sensitivity, and hepatic steatosis.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%